STUDY OF VARIOUS INDICES OF THE HUMAN SACRUM FOR SEX DETERMINATION - SAKTIDEVI. R (The Bioscan, 2025)
INTRODUCTION: The human pelvis shows marked sexual dimorphism & is used for the identification and sexing of an individual. Among the pelvic bones, sacrum forms an integral part to study the sexual dimorphic characters[Elkhateeb et al (1)]. The sacral length, sacral breadth, dimensions of first sacral vertebra, play a crucial role in sex determination particularly in dealing with incomplete skeletal remains[Ravichandra et al (2)]. MATERIAL AND METHODS: The study was conducted on 73 dry human sacra, of unspecified sex. The gender was determined by using the length of the sacrum, width of the sacrum, transverse diameter of the body of 1st sacral vertebra, anteroposterior diameter of the body of the 1st sacral vertebra, and vertical diameter of the auricular surface by using vernier caliper.Sacral index, auricular index, corporobasal index, index of the body of S1 vertebra was also calculated. RESULTS: The mean sacral index is significantly higher in females (113.90 mm) than in males (97.33 mm) The mean corporobasal index is higher in male (46.63 mm) than in females (43.48 mm) . The mean index of the body of S1 vertebra is higher in male (66.09 mm) than in females (63.04 mm). The mean auricular index was higher in male (55.44 mm) than in females (52.61 mm). CONCLUSION: Sacral index was significantly more in females than males and is reliabletool for sexing of the sacra. Key words Length of sacrum, width of sacrum, auricular index.